2021
DOI: 10.1155/2021/3456725
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin Induces Ferroptosis in HCC by Promoting the Formation of PEBP1/15‐LO

Abstract: Relevant researches have recognized the vital role of inducing ferroptosis in the treatment of tumor. The latest findings indicate that PEBP1/15-LO can play an essential role in the process of cell death. However, its role in regulating ferroptosis in hepatocellular carcinoma (simplified by HCC) remains unclear. The previous research of our team has proved that DHA can induce ferroptosis of hepatic stellate cells. In this study, we found that DHA could also induce ferroptosis in HCC cells. Interestingly, DHA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…A variety of factors can induce HCC; however, most HCCs are associated with hepatitis B virus infection, especially in China ( 2 ). Surgery is the first-line treatment for HCC ( 3 ). Yet, due to the lack of early specific symptoms, most patients are diagnosed at the middle or advanced stage, thus missing the opportunity for surgical treatment ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of factors can induce HCC; however, most HCCs are associated with hepatitis B virus infection, especially in China ( 2 ). Surgery is the first-line treatment for HCC ( 3 ). Yet, due to the lack of early specific symptoms, most patients are diagnosed at the middle or advanced stage, thus missing the opportunity for surgical treatment ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…[167] proved artesunate to be an effective and specific ferroptosis activator as well as a novel pathway for killing pancreatic cancer cells. In HCC cells, another derivate of artemisinim, dihydroartemisinin (DHA), was shown to induce ROS accumulation and thus ferroptosis, leading to reduced HCC development in a dose-dependent manner both in vitro and in vivo [206]. Recently, a synergistic mode of action was also proven for the combined treatment of sorafenib and artesunate in HCC cell lines in vitro and in vivo [207].…”
Section: Other Classesmentioning
confidence: 99%
“…For instance, magnesium isoglycyrrhizinate, derivatives of artemisinin (such as artemether, artesunate, and dihydro-artemisinin (DHA)), wild bitter melon extracts, chrysophanol, and zalkaloid berberine could block the development of liver fibrosis by triggering HSC ferroptosis [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ]. Besides, several studies revealed that DHA could trigger ferroptosis to block HCC growth by promoting PEBP1/15LO formation or an unfolded protein response [ 153 , 154 ]. Moreover, DHA and artesunate could enhance the anti-tumor efficacy of sorafenib on HCC by inducing ferroptosis [ 155 , 156 ].…”
Section: Cell Death In Liver Diseasesmentioning
confidence: 99%